Application of frustration-aggression theory in curbing fulani-herdsmen insurgency and sustainability of livelihood in Benue and Plateau States of The North-Central Nigeria - Daniel Mevayerore Igbini; Vincent Efebeh; Victor Esekumemu Clark (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
In-depth discussion of the Frustration-Aggression theory is provided in this study. The investigation used secondary data taken from books and articles that were already published. The conflict between Fulani herdsmen and farmers in Nigeria's North-Central, particularly in Benue and Plateau States, and now in other geopolitical zones of the country, is evidence of this theory's modest effort to explain why people engage in aggressive behavior, which in most cases results in violent conflict situations. The theory holds that while farmers view land as their private property that needs to be protected, herders view it as an open space that can be used and must be used to feed their livestock. As a result, the encroachment into lands assigned to farmers is believed to be the result.